The endoplasmic reticulum, calcium signaling and junction turnover in Sertoli cells. Issue 2 (February 2018) - Vogl, Wayne; Lyon, Kevin; Adams, Arlo; Piva, Matthew; Nassour, Vanessa
Abstract : The endoplasmic reticulum (ER) forms a continuous network throughout morphologically differentiated Sertoli cells. It is an integral component of intercellular adhesion junctions in this cell type, as well as forming membrane contact sites with the plasma membrane and intracellular organelles. One of the major functions of the ER in cells generally is maintaining calcium homeostasis and generating calcium signals. In this review, we discuss what is currently known about the overall pattern of distribution of the ER in Sertoli cells and the location of calcium regulatory machinery in the various subdomains of the organelle. Current data are consistent with the hypothesis that calcium signaling by the ER of Sertoli cells may play a significant role in events related to junction remodeling that occur in the seminiferous epithelium during spermatogenesis.